Biocompatibility evaluation of antibacterial Ti–Ag alloys with nanotubular coatings - Liu X (Dove Medical Press, 2019)
Xingwang Liu,1,2,* Chen Chen,3,* Hangzhou Zhang,4 Ang Tian,5 Junhua You,6 Lin Wu,7 Zeming Lei,8 Xi Li,8 Xizhuang Bai,8 Shiyi Chen1 1Department of Sports Medicine, Huashan Hospital of Fudan University, Shanghai 200040, China; 2State Key Laboratory of Molecular Engineering of Polymers, Fudan University, Shanghai 200082, China; 3Department of Arthroscopic Surgery, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai 200233, China; 4Department of Sports Medicine and Joint Surgery, The First Affiliated Hospital of China Medical University, Shenyang 110000, China; 5Liaoning Provincial Key Laboratory of Metallurgical Resources Circulation Science, Northeastern University, Shenyang 110819, China; 6School of Materials Science and Engineering, Shenyang University of Technology, Shenyang 110870, China; 7Department of Prosthodontics, School of Stomatology, China Medical University, Shenyang 110000, China; 8Department of Orthopaedics, The People’s Hospital of China Medical University, Shenyang 110000, China *These authors contributed equally to this work Background: Implant-related infection is a major problem postsurgery. As an alternative to a localized antibiotic release system, we used Ag to fabricate Ti–Ag alloys with nanotubular coatings (TiAg-NTs). Ag has excellent antibacterial properties, but its biological toxicity is a concern. Therefore, we performed biological experiments both in vitro and in vivo to evaluate the biocompatibility of TiAg-NTs with different concentrations of Ag (1%, 2%, and 4%). Methods: For in vitro experiments, cytocompatibility, including cell attachment, viability, and proliferation, was tested, and genes and proteins related to osteogenic differentiation were also evaluated. For in vivo assays, the rat femoral condylar insertion model was used, and micro-computed tomography (micro-CT) and histological analysis were conducted to analyze bone formation around implants at 1, 2, and 4 weeks after surgery. Results: Both in vitro and in vivo results indicate that Ti2%Ag-NT showed comparable cytocompatibility with commercially pure Ti (cp-Ti), and it could achieve good osseointegration with the surrounding bone tissue. Conclusion: We thus believe that Ti2%Ag-NT is a potential biomaterial for orthopedics. Keywords: Ag, Ti, alloy, nanotube, biocompatibility